From beak to fruit: An Asian hornbill database for frugivory and seed dispersal research - Hanci Liang; Kim R. McConkey; Jun Ying Lim (Global Ecology and Conservation, 2024)
Hornbills (family Bucerotidae) are important frugivores and seed dispersers of Asian tropical forests. While much is known about the diets and their role as seed dispersers at the local or landscape scale, the lack of a comprehensive, standardised, and digital database on hornbill frugivory and seed dispersal interactions hampers broader and comparative studies across hornbill species and with other avian frugivore groups. To fill this crucial gap, we compiled a species-level database of plant-hornbill interactions in tropical Asia from primary sources throughout the literature; the database consisting of 2365 interaction records for 26 Asian and New Guinea hornbill species (out of the 32, or 80% of, species), a testament to the efforts of numerous hornbill biologists and ecologists. Fruits or seeds from 471 plant species, 240 genera and 84 families were reported to be consumed. Significant gaps in data coverage, however, remain. Rarefaction curves based on interaction records are not strongly saturating, revealing the scale of the “Eltonian shortfall”, that is, the paucity of species interaction information for many species. Our database also reveals a dearth in information on seed fate of hornbill consumed fruits and seeds. While approximately 58% of the interaction records provided were implied or reported to be associated with seed removal, only about 26% and 1% of studies provide any indication of seed deposition and post-depositional seed viability, respectively. To conclude, we briefly illustrate the value of the dataset for investigating broad patterns in hornbill frugivory. By combining our dataset with complementary hornbill beak and plant trait data, we show that hornbills consume and potentially disperse seeds of many plant species that would be beyond the physical capabilities of other avian frugivores. We were also able to recover a positive relationships between hornbill beak sizes and the size of the fruits and seeds they consumed though the patterns were generally weak, possibly due to the low sample size and afore-mentioned gaps in data coverage. In light of these data gaps, it is clear that more hornbill frugivory and seed dispersal research is needed, and we hope that our database will be a valuable, central resource for future hornbill research.